2006
DOI: 10.1249/01.mss.0000227542.43669.45
|View full text |Cite
|
Sign up to set email alerts
|

Development of Novel Techniques to Classify Physical Activity Mode Using Accelerometers

Abstract: The novel approach of estimating activity mode, rather than activity level, may allow for more accurate field-based estimates of physical activity using accelerometer data, and this approach warrants more study in a larger and more diverse population of subjects and activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
167
2
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(171 citation statements)
references
References 32 publications
1
167
2
1
Order By: Relevance
“…Advances have, however, been made in accelerometer data processing with the development of more sophisticated approaches to data modelling analysis (Bonomi et al 2009, Pober et al 2006, Staudenmayer et al 2009, Zhang et al 2003. This area warrants further investigation in studies of pre-school children to determine if this will offer an accurate means of classifying physical activity behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…Advances have, however, been made in accelerometer data processing with the development of more sophisticated approaches to data modelling analysis (Bonomi et al 2009, Pober et al 2006, Staudenmayer et al 2009, Zhang et al 2003. This area warrants further investigation in studies of pre-school children to determine if this will offer an accurate means of classifying physical activity behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…1 Pober et al (2006) did compare the use of cut points to more advanced methods. However, they used counts, and not raw data, for all analyses.…”
Section: Discussionmentioning
confidence: 99%
“…In principle, different methods are suited for classification (for an extensive overview of classification techniques, see Preece et al, 2009). The methods used include k-nearest neighbor (e.g., Bao & Intille, 2004;Zhang, Rowlands, Murray, & Hurst, 2012), hidden Markov models (e.g., Pober, Staudenmayer, Raphael, & Freedson, 2006), and artificial neural networks (e.g., Hagenbuchner, Cliff, Trost, van Tuc, & Peoples, 2015;Staudenmayer, Pober, Crouter, Bassett, & Freedson, 2009). The Bstate-of-the-art^method that has proven effective for such tasks is the use of support vector machines (SVMs; e.g., He & Jin, 2009).…”
mentioning
confidence: 99%
“…Generic activity categories are classified with a relatively small number of accelerometers. Pober et al 53 reported an accuracy of 81% for identifying walking and certain lifestyle activities, like vacuum cleaning and working on a computer, Activity monitoring and health AG Bonomi and KR Westerterp by using an Actigraph accelerometer (Actigraph). We showed that identifying three different postures, that is, lying, sitting and standing, and three types of locomotion movements, that is, walking, running and cycling, was accurately achieved using a single accelerometer positioned at the waist.…”
Section: Activity Recognition Using Multiple or Single-site Accelerommentioning
confidence: 99%